EAS Elements for Solid Mechanics Mesh Distortion Insensitive and Hourglassing-Free Formulations with Increased Robustness - Pfefferkorn, Robin (Schriftenreihe des Instituts für Mechanik, Karlsruher Institut für Technologie, 2023)
Proposed in the early 1990s, the enhanced assumed strain (EAS) method is one of the probably most successful mixed finite element methods for solid mechanics. This cumulative dissertation gives a comprehensive overview of previous publications on that method and covers recent improvements for EAS elements. In particular, we describe three key issues of standard EAS elements and develop corresponding solutions.